2022
DOI: 10.3390/vaccines10010069
|View full text |Cite
|
Sign up to set email alerts
|

Design and Immunological Properties of the Novel Subunit Virus-like Vaccine against SARS-CoV-2

Abstract: The COVID-19 pandemic is ongoing, and the need for safe and effective vaccines to prevent infection and to control spread of the virus remains urgent. Here, we report the development of a SARS-CoV-2 subunit vaccine candidate (Betuvax-CoV-2) based on RBD and SD1 domains of the spike (S) protein fused to a human IgG1 Fc fragment. The antigen is adsorbed on betulin adjuvant, forming spherical particles with a size of 100–180 nm, mimicking the size of viral particles. Here we confirm the potent immunostimulatory a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…As a result of the pandemic of the new coronavirus infection SARS-CoV-2, there is the demand for disinfecting agents and hand sanitizers based on Ag NPs due to their pronounced antiviral properties [20]. In addition, a COVID-19 vaccine containing spherical NPs as the carrier has been patented [21]. It is known that many synthesis technologies can be used for the relatively inexpensive commercial production of spherical Ag NPs.…”
Section: Uses Of Silvermentioning
confidence: 99%
“…As a result of the pandemic of the new coronavirus infection SARS-CoV-2, there is the demand for disinfecting agents and hand sanitizers based on Ag NPs due to their pronounced antiviral properties [20]. In addition, a COVID-19 vaccine containing spherical NPs as the carrier has been patented [21]. It is known that many synthesis technologies can be used for the relatively inexpensive commercial production of spherical Ag NPs.…”
Section: Uses Of Silvermentioning
confidence: 99%
“…The study of immunogenic properties of the “Betuvax-CoV-2” vaccine has proved its ability to stimulate both humoral and cellular immune response. Previously we showed [7] that double immunization of mice led to the formation of an adaptive T-cell immune response. We observed an increase in both CD4+ and CD8+ Tem spike-specific cells after two administrations.…”
Section: Discussionmentioning
confidence: 99%
“…We have developed a subunit virus-like vaccine “Betuvax-CoV-2” against the SARS-CoV-2 based on the RBD and the SD1 domain of the S1 protein, fused with the human IgG1 Fc-fragment. This coronavirus antigen is being absorbed on the surface of betulin-based spherical particles 100–180 nm in size, mimicking the SARS-CoV-2 [7]. In the present paper, we have summarized the preclinical findings of the “Betuvax-CoV-2” vaccine on its safety, immunogenicity, and protectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…The antigen is expressed in CHO cells, adsorbed on a plant-derived adjuvant, betulin (pentacyclic triterpenoid) that forms spherical particles (betuspheres). The authors showed that the vaccine induced the production of high titers of antibodies (RBD-specific and SARS-CoV-2-neutralizing) and the development of T cell immunity in mice [ 133 ]. The Betuvax-CoV-2 vaccine is undergoing phase 1/2 clinical trials (NCT05270954).…”
Section: Recombinant Covid-19 Vaccinesmentioning
confidence: 99%